2021
DOI: 10.1136/jmedgenet-2020-107595
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic spectrum and genomics of undiagnosed arthrogryposis multiplex congenita

Abstract: BackgroundArthrogryposis multiplex congenita (AMC) is characterised by congenital joint contractures in two or more body areas. AMC exhibits wide phenotypic and genetic heterogeneity. Our goals were to improve the genetic diagnosis rates of AMC, to evaluate the added value of whole exome sequencing (WES) compared with targeted exome sequencing (TES) and to identify new genes in 315 unrelated undiagnosed AMC families.MethodsSeveral genomic approaches were used including genetic mapping of disease loci in multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…Genetic neuromuscular and developmental disorders with onset in the first year of life include a variety of monogenic conditions, including AMC, with expanding clinical differential diagnosis, genetic heterogeneity, and associated disease mechanisms (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic neuromuscular and developmental disorders with onset in the first year of life include a variety of monogenic conditions, including AMC, with expanding clinical differential diagnosis, genetic heterogeneity, and associated disease mechanisms (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Although over 320 genes have been implicated, exemplifying the genetic heterogeneity of the condition (115), AMC is poorly related to SCN1A, with only two reports documented (93,94). The first report described SCN1A mutations in three infants with AMC from three different families (93).…”
Section: Arthrogryposis Multiplex Congenitamentioning
confidence: 99%
“…Exome sequencing is reported to have a diagnostic yield of 47% to 73% in large MCC cohorts, and a recent study with 315 unrelated families showed that 21% of the variations resided in recently identified genes. [3][4][5][6] This report defines a new recessive antenatal MCC phenotype with underdevelopment of the corpus callosum and dysmorphic features, associated with a homozygous frameshift variant in ubiquitinspecific protease 14 (USP14, MIM 607274) in three fetuses from two related families investigated using exome sequencing. In line with the clinical presentation of the affected cases reported here, mice models deficient for the USP14 ortholog have been shown to display early lethality, muscle wasting, and callosal defects.…”
mentioning
confidence: 93%
“…The vast majority of these fetal conditions are of genetic origin, and to date, more than 400 distinct disorders with MCC have been described. Exome sequencing is reported to have a diagnostic yield of 47% to 73% in large MCC cohorts, and a recent study with 315 unrelated families showed that 21% of the variations resided in recently identified genes 3–6 …”
Section: Introductionmentioning
confidence: 99%